(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the study of mythological ornithonymy in English philology. In particular, similar and different aspects of the image of birds in fairy tales are analyzed in Uzbek and English folklore. There are also stories about dragons and mythological birds of the Altai Turks.